Toe to toe : a novel - Ballard, Falon (G.P. Putnam's Sons, 2026)
"Allegra Hart has been working her whole life to achieve one goal: become a principal ballerina. When her director starts holding auditions for the lead role in the company's latest production, Allegra sees this as her chance-maybe her last chance. The catch? The director wants someone with sex appeal, and he doesn't think she's up to the task. Determined to prove him wrong, Allegra enlists the help of the lead dancer of an all-male revue, Cord Donovan, a classically trained dancer who is also the sexiest man she's ever met. In exchange for lessons on how to ramp up her sex appeal, she promises to help Cord choreograph a new partner piece for his show. As they practice their moves on and off the stage, Allegra and Cord find themselves battling a growing attraction, all the more illicit because Cord has sworn to never partner with a ballerina. Allegra is determined not to let a man derail her career, but what if she could have both love and success? Or will her involvement with Cord jeopardize everything she's worked for?"-- Provided by publisher.